Server Farms and XML Web Service - Thelin, Jorgen; Murray, PJ (2002)
What aspects must a developer be aware of when a Web Services will be run in clustered environment such as a server farm? Do Web Services implementations need to be "cluster aware", or can this be handled transparently by the runtime platform? We revisit the subject of why keeping Web Services implementations as stateless as possible really helps in these circumstances, and the effect of using session-based facilities on scalability.
Presented at LinuxWorld Conference & Expo Conference, August 2002, San Francisco, CA, USA